Design of PLC-based system for linearity output voltage of ACDC converter - Sawai Pongswatd; Krit Smerpitak; Farzin Asadi; Teerawat Thepmanee (My University, 2021)
This paper presents the PLC-Based system for controlling the SCR power module which is AC–DC converter proposes to linearity output voltage with trigger signal. The technique converted the trigger signal by arccosine function and analog module in the PLC. Converted signal from PLC system is fed to SCR power module instant the traditional signal. Proposed of this paper describes the PLC hardware configuration, compute/math and trigonometric functions with Studio 5000 software. In addition, the interfacing, parameters configuration, and monitoring are considered for testing. The technique with PLC-based, devices configuration and experimental results have been presented will be useful for electric power supply in the industry with more and more demand to apply the PLC system to develop the traditional industry to semi or automatic control in the industry.
Keywords: Interfacing; SIGNAL (programming language); Linearity; Industrial Automation and Control Systems